A behavioral macroeconomic model of exchange rate fluctuations with complex market expectations formation - Peter Flaschel; Florian Hartmann; Chris Malikane; Christian R. Prosano (Osnabrück University, Institute of Empirical Economic Research, 2013)
The paper investigates the emergence of complex market expectations (opinion dynamics) around nominal exchange rate adjustments using a macro-financial model of a small open economy featuring heterogeneous expectation formation (chartists and fundamentalists) and gradual adjustment processes in real and also to a certain degree in financial markets. The model shows among other things the mechanisms through which the first type of agents tends to destabilise the economy. Global stability can be ensured if opinions turn to fundamentalist behaviour far off the steady state. This interaction of expectations and population dynamics is bounding the - due to chartist behavior - potentially explosive real-financial market interactions, but can enforce irregular behaviour within these bounds. The size of output and exchange rate fluctuations can be dampened by adding suitable policy measures to the dynamics of the private sector.
Keywords: E12; E24; E31; E52; 330; Nonlinear Exchange Rate Dynamics; Opinion Dynamics; Viability; Persistent and Irregular Fluctuations; Macroeconomic Policy